2021
DOI: 10.1088/0256-307x/38/1/018701
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Evaluation on the Interactions of SARS-CoV-2 with Its Receptor ACE2 and Antibodies CR3022/CB6*

Abstract: The spread of the coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has become a global health crisis. The binding affinity of SARS-CoV-2 (in particular the receptor binding domain, RBD) to its receptor angiotensin converting enzyme 2 (ACE2) and the antibodies is of great importance in understanding the infectivity of COVID-19 and evaluating the candidate therapeutic for COVID-19. We propose a new method based on molecular mechanics/Poisson–Boltzmann sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 53 publications
4
42
0
Order By: Relevance
“…After the RBD was stably absorbed, the last 30 ns of the simulated trajectory was used to calculate the binding free energy by the shell script gmx_mmpbsa [57] , [68] , with one frame at 1 ns interval. The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the RBD was stably absorbed, the last 30 ns of the simulated trajectory was used to calculate the binding free energy by the shell script gmx_mmpbsa [57] , [68] , with one frame at 1 ns interval. The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The binding energy (BE) of each residue with graphene was also calculated using gmx_mmpbsa [57] , [68] , where the energy contributed by entropy was not included. The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, CR3022 has been suggested as a promising therapeutic option to neutralize SARS-CoV-2 (Barnes et al, 2020;Tian et al, 2020;Wu et al, 2020;Yuan et al, 2020), and is often explored in theoretical studies (Corrêa Giron et al, 2020;Ding et al, 2021;Nguyen et al, 2021;Shariatifar and Farasat, 2021). In a pioneer computational study at the very beginning of the pandemic, using constant-pH MC simulations, Giron, Laaksonen, and Barroso da Silva showed that CR3022 known to bind to SARS-CoV-1 RBD could also bind to SARS-CoV-2 RBD.…”
Section: Some Previous Theoretical Studies With Cr3022mentioning
confidence: 99%
“…64 In the binding energy calculation, the last 10 ns of each stabilized simulation trajectory was used with an interval of 100 ps, namely 100 frames for each run using the molecular mechanics Poisson-Boltzmann surface area (MMPBSA) method. [65][66][67][68][69] The gmx_mmpbsa script (https://jerkwin.github.io/ gmxtool) together with the APBS 70,71 program were used to calculate the binding energy and the corresponding energy decomposition term, namely the electrostatic (ELE) energy, the van der Waals (VDW) energy, and the solvation energy including the polar part (PB) and the non-polar part (SA) in this work.…”
Section: Model and Methodsmentioning
confidence: 99%